Experimental and computational exploration of photophysical and electroluminescent properties of modified 2, 2′:6′, 2″‐terpyridine, 2, 6‐di(thiazol‐2‐yl)pyridine and 2, 6‐di(pyrazin‐2‐yl)pyridine ligands and their Re(I) complexes. (9th October 2018) - Klemens, Tomasz; Świtlicka, Anna; Szlapa‐Kula, Agata; Krompiec, Stanisław; Lodowski, Piotr; Chrobok, Anna; Godlewska, Magdalena; Kotowicz, Sonia; Siwy, Mariola; Bednarczyk, Katarzyna; Libera, Marcin; Maćkowski, Sebastian; et al.
Abstract : The excited‐state characteristics of a series of 2, 2′:6′, 2″‐terpyridine (terpy), 2, 6‐di(thiazol‐2‐yl)pyridine (dtpy) and 2, 6‐di(pyrazin‐2‐yl)pyridine (dppy) derivatives as well as their corresponding Re(I) complexes [ReCl(CO)3 (L n ‐κ 2 N)] were investigated both experimentally and theoretically, and the crucial effect of pyrrolidine substituent and peripheral rings on the optical and electrochemical properties was found evident. For Re(I) complexes bearing the ligands with electron‐rich pyrrolidine substituent, different emission profiles were found in polar and non‐polar solvents, indicating a change in the character of the excited state. Dual‐emission effect of [ReCl(CO)3 (L 4 ‐κ 2 N)] and [ReCl(CO)3 (L 5 ‐κ 2 N)] in chloroform was attributed to the presence of two emitting states, identified as an 1 ILCT excited state deactivated at higher energies and a longer‐lived red‐shifted phosphorescence assigned to the 3 MLCT excited state. The triplet excited state was confirmed by recording the nanosecond time‐resolved transient absorption spectra for the compound [ReCl(CO)3 (L 4 ‐κ 2 N)]. To verify the charge transfer problem of low‐lying excited states of the free ligands, the Λ parameter was calculated. In addition, the compounds were applied as emitting layers for both non‐doped and doped single‐layer organic light‐emitting diodes fabricated by solution processing. Abstract : The excited‐state characteristics of a series of triimine ligands as well as their corresponding Re(I) complexes were investigated experimentally and theoretically.